Anticancer activity and apoptotic induction of Chromolaena odorata Linn leaves extract and fractions on hepatocellular carcinoma cell lines (HepG2) - HANIFAH YUSUF; MARHAMI FAHRIANI (Jurnal Natural, 2022)
The purpose of this study is to screen and to evaluate anticancer activity and apoptosis induction of Chromolaena odorata (C. odorata) leaves extract and its fractions on HepG2 cancer cell lines. The C. odorata leaves were extracted by maceration using ethanol 80% then fractionated by using n-hexane, ethyl acetate and ethanol. MTT assay method was used to evaluate anticancer activity and flowcytometri method used to evaluate the induction of apoptosis. The phytochemical analysis and  characterization of the major compound of the extract and the fractions were done by using Liquid Chromatography-Mass Spectroscopy (LCMS). The phytochemical analyis showed that the crude ethanolic extract and fractions of C. odorata leaves contains alkaloid, flavonoids, phenolic, steroids, tannin and saponin. The result of LCMS shown the major compounds of the extract and fractions are 5,7,8,3′,4′-Pentamethoxyflavonone, 1-Carboethoxy-β-carboline, 3-Methylcanthin-2, 6- dion, Canthin-6-one. In the n-hexane fraction obtained 5,7,8,3′,4′-Pentamethoxyflavonone, Methyl ophiopogonanone A and Pd-C-Ⅱ. Meanwhile, in the ethyl acetate fraction contained, 3-(3′,4′-Dihydroxybenzyl)-7-hydroxychroman-4-one, 3-(4'-Hydroxy-benzyl)-5,7-dihydroxy-6-methyl-8- methoxy-chroman-4-one, Methyl opiopogonanone A and Sinensetin. The ethanol fraction, contained the compound 3-(3′,4′-Dihydroxybenzyl)-7-hydroxychroman-4-one, 3-(4'-Hydroxy-benzyl)-5,7-dihydroxy-6-methyl-8- methoxy-chroman-4-one and Methyl opiopogonanone A. The crude ethanolic extract, n-hexane fraction, ethyl acetate and ethanol fraction extract have anticancer activities with IC50 value of 23.44 mg/mL, 84.52mg/mL; 88.51mg/mL; and 167.49 mg/mL respectively. This research suggests the crude ethanolic extract of Chromolaena odorata leaves has a potential candidate for hepatocarcinoma treatment.